Tinjauan Kelengkapan Pengisian Persetujuan Tindakan Kedokteran Pada Pasien Rawat Inap di Rumah Sakit Yadika Kebayoran Lama - Redha Maulina; Indah Kristina; Rury Agnesia (APIKES Bhumi Husada Jakarta, 2018)
ABSTRACT From the results of observations at YadikaKebayoran Lama Hospital, none of the medical action approval forms were filled in completely. The purpose of this study was to obtain an overview of completing the approval form for medical treatment for inpatients at YadikaKebayoran Lama Hospital. The type of research used is descriptive. The method used is observation and interview. The study population was 128 medical action approval forms. Based on the results of a quantitative analysis of 128 approval forms of medical action, the results were filled in completely by 88.47% and those not filled in completely by 11.53%. of the 4 components of the quantitative analysis criteria the most complete percentage analysis is found in the patient's identity at 100% while the lowest percentage is in the good recording of 75%. Based on interviews conducted with the head of the medical record at YadikaKebayoran Lama Hospital there are several factors that cause incompleteness in filling out medical action approval forms, namely SPO (Standard Operating Procedures) used are still Informed Consent and lack of understanding of officers in the inpatient room when filling out medical action approval forms. So the author gives suggestions for revision of existing SPO (Standard Operating Procedures) and re-socialized to officers in the inpatient room to fill in the complete in the incomplete parts such as important reports, good authentication and recording. It is expected that officers in the inpatient room, either room doctors / nurses, are related to filling out approval forms for medical actions to fill in completely, especially on the authentication component and important reports on the information content section. Keyword: Medical Action Approval Form ABSTRAK Dari hasil observasi di Rumah Sakit Yadika Kebayoran Lama tidak ada satu pun formulir persetujuan tindakan kedokteran yang diisi dengan lengkap. Tujuan dari penelitian ini adalah memperoleh gambaran kelengkapan pengisian formulir persetujuan tindakan kedokteran pasien rawat inap di Rumah Sakit Yadika Kebayoran Lama. Jenis penelitian yang digunakan adalah deskripstif. Metode yang digunakan adalah observasi dan wawancara. Populasi penelitian adalah 128 formulir persetujuan tindakan kedokteran. Berdasarkan hasil analisa kuantitatif terhadap 128 formulir persetujuan tindakan kedokteran di peroleh hasil yang diisi dengan lengkap sebesar 88.47% dan yang tidak diisi dengan lengkap sebesar 11.53%. dari 4 komponen analisa kuantitatif kriteria analisa jumlah persentase terlengkap terdapat pada identitas pasien sebesar 100% sedangkan persentase terendah terdapat pada pencatatan yang baik sebesar 75%. Berdasarkan wawancara yang dilakukan dengan kepala rekam medis di RumahSakit Yadika Kebayoran Lama terdapat beberapa faktor penyebab ketidaklengkapan pengisian formulir persetujuan tindakan kedokteran yaitu SPO (Standar Prosedur Operasional) yang digunakan masih Informed Consent dan kurang pahamnya petugas di ruang rawat inap dalam pengisian formulir persetujuan tindakan kedokteran. Maka penulis memberikan saran untuk di revisi kembali SPO (Standar Prosedur Operasional) yang sudah ada dan disosialisasikan kembali kepada petugas di ruang rawat inap untuk mengisi dengan lengkap pada bagian yang masih belum lengkap seperti laporan penting, autentifikasi dan pencatatan yang baik. Diharapkan petugas di ruang rawat inap baik itu dokter ruangan/perawat terkait pengisian formulir persetujuan tindakan kedokteran untuk mengisi dengan lengkap khususnya pada komponen autentifikasi dan laporan penting pada bagian isi informasi. Kata Kunci: Formulir Persetujuan Tindakan Kedokteran